Of course people can reject democracy: psychological perspectives - Newman, Leonard S. (Frontiers in Social Psychology, 2024)
Concerns have been expressed about a worldwide retreat from liberal democracy and a turn towards more authoritarian forms of government. Along with that concern has come surprise: when the cold war ended, it was widely believed that a new historical era was dawning during which alternatives to Western liberalism would wither away. Influential psychological theories also assume that freedom and autonomy are powerful human needs-needs that are thwarted by dictatorships. However, a number of theoretical perspectives and programs of research in psychology lead to the conclusion that in certain circumstances, turns toward authoritarian forms of government and restrictive societies are not only explicable, but also predictable. Fromm's analysis of why people might want to escape from freedom, Baumeister's work on escape-from-self mechanisms, and Schwartz's review of the literature on choice overload all provide ways of understanding why in turbulent times, members of free countries might intentionally seek out--and perhaps even ecstatically embrace--authoritarian forms of government.